If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 3x + -6x + -3 Reorder the terms: 15 = -3 + 3x + -6x Combine like terms: 3x + -6x = -3x 15 = -3 + -3x Solving 15 = -3 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 15 + 3x = -3 + -3x + 3x Combine like terms: -3x + 3x = 0 15 + 3x = -3 + 0 15 + 3x = -3 Add '-15' to each side of the equation. 15 + -15 + 3x = -3 + -15 Combine like terms: 15 + -15 = 0 0 + 3x = -3 + -15 3x = -3 + -15 Combine like terms: -3 + -15 = -18 3x = -18 Divide each side by '3'. x = -6 Simplifying x = -6
| 6y^2+8y-9y-12= | | X+x+1+x+2=274 | | -36=p-6 | | 3=18x+6x^2 | | G(x)=8sin(5x^6) | | 6y^2+8y-8y-12= | | k^2+12k=-35 | | 2x^3-2x^2+7x-40=0 | | 9d+d-d+2-3d=0 | | 6y^2+8y-12= | | (49x^2)-(25)=0 | | 3(x+y)-2(2y+x)+y= | | 1+n/3=-6 | | 2x+8+2x=10+2x+12 | | 1.2+y=-8 | | 4x-5=6x-13 | | 5-(x+3)+3x+3(x+2)= | | -18+12-3= | | (9x+9)+(-12x+24)= | | 4(x+3)+(x+6)+2(x-3)= | | 160s+465(88-s)=19265 | | n^2+14n-95=0 | | 0=7x-28 | | (x-5i)(x+5i)=0 | | 2x+y-3x+4y-6+5y= | | 1/3(2x+9)=2/3x+3 | | 5x+20=15+10x | | a-16=2(3-a) | | 9y=18x-54 | | 2p+9-8p=3p-18 | | 3(x+2)=2(x+1)-5 | | 8y-6=4y-18 |